2000
DOI: 10.1007/s005350070031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Helicobacter pylori infection on Zollinger-Ellison syndrome

Abstract: Both Zollinger-Ellison syndrome (ZES) and Helicobacter pylori infection are major etiologic factors for peptic ulcer. The aim of this study was to investigate the effect of H. pylori infection on ZES with special reference to acid secretion. Sixteen patients with ZES were selected (median age, 59 years; range, 39-66 years; M/F, 9/7), and H. pylori status, ulcer location, gastric acid secretion, serum pepsinogen (PG) I and II concentrations, and PG I/II ratio were determined. The seroprevalence of H. pylori inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
6
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…As in several previous reports on ZES, Watanabe et al 5 have shown acid secretion to be lower in H. pyloripositive patients than in H. pylori-negative patients. They suggested two possible mechanisms for gastric acid secretion in H. pylori-positive patients; i.e., H. pylori-induced atrophic gastritis and a direct inhibitory action of H. pylori on parietal cells.…”
supporting
confidence: 70%
See 4 more Smart Citations
“…As in several previous reports on ZES, Watanabe et al 5 have shown acid secretion to be lower in H. pyloripositive patients than in H. pylori-negative patients. They suggested two possible mechanisms for gastric acid secretion in H. pylori-positive patients; i.e., H. pylori-induced atrophic gastritis and a direct inhibitory action of H. pylori on parietal cells.…”
supporting
confidence: 70%
“…Current views are that H. pylori infection is often acquired in childhood, but that age at onset of ZES is under 20 years in fewer than 10% of the patients. 5,7,13 The similar seroprevalence of H. pylori in patients with ZES and in the general population also points to this factor. Watanabe et al 5 reported no difference in gastric acid secretion between seropositive and seronegative patients with H. pylori-negative ZES, but they found that serum pepsinogen I levels were significantly higher in the seronegative than in the seropositive patients.…”
mentioning
confidence: 70%
See 3 more Smart Citations